Preliminary Numerical Estimation of Selected Terminal Ballistic Effects Produced by Explosion of Mortar Projectile - Bartosz FIKUS (Wstępne oszacowania numeryczne wybranych efektów balistyki końcowej powstałych na skutek wybuchu pocisku moździerzowego, 2018)
Results of theoretical modelling of mortar projectile’s fragments propulsion were shown. Taking into account universality of application of the considered ammunition, it seems to be reasonable to conduct simulations of projectile’s fragments propulsion and interaction with the environment. In the conducted investigations, due to dynamic character of the whole phenomena, characterized by extremely high values of strains and strain’s rate, the meshless explicit approach was used (Smoothed Particle Hydrodynamics method implemented in AUTODYN software). This approach minimalized the negative effects of deformation of “classical” Lagrangian mesh. In order to validate a numerical model, the results were compared with the simplified Gurney’s formula, which provides high accuracy of fragment’s velocity for regular shapes of casing. Comparison of the results showed low value of relative discrepancy (lower than 10%) for the cylindrical part of the casing in which detonation was fully developed and resulted in higher values of relative discrepancy of initial velocity for the non – cylindrical region, especially where the detonation was not developed.
Keywords: Balistyka końcowa pocisku moździerzowego